4, 5‐dicaffeyolquinic acid improves high‐fat diet‐induced cognitive dysfunction through the regulation of insulin degrading enzyme. Issue 7 (11th April 2019) - Kang, Jin Yong; Park, Seon Kyeong; Kim, Jong Min; Park, Su Bin; Yoo, Seul Ki; Han, Hye Ju; Kim, Dae Ok; Heo, Ho Jin
Abstract: This study was performed to investigate the effects of Artemisia argyi and 4, 5‐dicaffeyolquinic acid (4, 5‐diCQA) as a main compound of ethyl acetate fraction from Artemisia argyi (EFAA) on high‐fat diet (HFD)‐induced cognitive dysfunction. Both EFAA and 4, 5‐diCQA were effective in improving cognitive function on HFD‐induced cognitive dysfunction. In brain tissue analysis, it was confirmed that EFAA and 4, 5‐diCQA inhibited the reduction of neurotransmitters as well as oxidative stress and mitochondrial dysfunction. In addition, they inhibited amyloid β (Aβ) accumulation by increasing the expression of insulin‐degrading enzyme and consequently prevented apoptosis. In conclusion, it is presumed that Artemisia argyi may help to improve the cognitive impairment due to the HFD, and it is considered that this effect is closely related to the physiological activity of 4, 5‐diCQA. Practical applications: Artemisia argyi is used in traditional herbal medicine in Asia. Type 2 diabetes mellitus has been proven by a variety of epidemiological studies to be a risk factor for cognitive impairment, such as Alzheimer's disease. This study confirmed that 4, 5‐diCQA is a bioactive compound of Artemisia argyi on improving HFD‐induced cognitive dysfunction. Therefore, this study can provide useful information to the effect of Artemisia argyi and related substance. Abstract : This study was performed to investigate the effects of Artemisia argyi and its main constituents (4, 5‐dicaffeyolquinic aicd; 4, 5‐diCQA) on high‐fat diet (HFD) induced cognitive impairment. Ethyl acetate fraction of Artemisia argyi (EFAA) and 4, 5‐diCQA were effective in improving cognitive function and inhibited the reduction of neurotransmitters as well as oxidative stress and mitochondrial dysfunction in brains. In addition, they inhibit amyloid β (Aβ) accumulation by increasing the expression of insulin degrading enzyme (IDE) and consequently prevent apoptosis in brain.